Role of Bentonite on the Mobility of Antibiotic Resistance Genes, and Microbial Community in Oxytetracycline and Cadmium Contaminated Soil - Guo, Honghong; Xue, Shuhong; Nasir, Mubasher; Lv, Jialong; Gu, Jei (Frontiers in Microbiology, 2018)
The effects of bentonite (BT), a commonly used heavy metal deactivator, on the ARGs and microbial communities in soils and lettuce systems contaminated by heavy metals and antibiotics are unclear. A study was conducted to investigate the effect of BT on the mobility of antibiotic resistance genes in oxytetracycline and cadmium contaminated soil. Results showed that the addition of BT reduced the accumulation of OTC and ARGs in the soil and lettuce roots, but increased the abundance of ARGs in lettuce leaves, and increase the risk of human pathogenic bacteria (HPB) transferring to lettuce leaves. Redundancy analysis showed that environmental factors (OTC, H2O, SOM and pH) were the dominant factors that influence the distribution of ARGs and intI1. Network analysis showed that Proteobacteria and Bacteroidetes were the major host bacteria which caused changes in ARGs and intI1. There were significant positive correlations between ermX and ermQ, and a large number of HPB. The co-occurrence of intl1 with some ARGs (tetC, tetG, ermQ, sul1, and sul2), may threaten human health due to the dispersion of ARGs via horizontal gene transfer.